Isthmocele: From Risk Factors to Management - Iannone, Piergiorgio; Nencini, Giulia; Bonaccorsi, Gloria; Martinello, Ruby; Pontrelli, Giovanni; Scioscia, Marco; Nappi, Luigi; Greco, Pantaleo; Scutiero, Gennaro (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2019)
Objective The aim of the present study was to perform a comprehensive review of the literature to provide a complete and clear picture of isthmocele—a hypoechoic area within the myometrium at the site of the uterine scar of a previous cesarean section—by exploring in depth every aspect of this condition.Methods A comprehensive review of the literature was performed to identify the most relevant studies about this topic.Results Every aspect of isthmocele has been studied and described: pathophysiology, clinical symptoms, classification, and diagnosis. Its treatment, both medical and surgical, has also been reported according to the actual literature data.Conclusion Cesarean section is the most common surgical procedure performed worldwide, and one of the consequences of this technique is isthmocele. A single and systematic classification of isthmocele is needed to improve its diagnosis and management. Further studies should be performed to better understand its pathogenesis.
Keywords: isthmocele; niche; cesarean section scar defect; hysteroscopy; laparoscopy